Ex vivo evaluation of the effects of a white grape juice extract on lymphocytic mitochondrial functions. Issue 4 (16th February 2020) - Visalli, Giuseppa; Ferlazzo, Nadia; Facciolà, Alessio; Picerno, Isa; Navarra, Michele; Di Pietro, Angela
Abstract: The physio-pathological role of mitochondria in aging and age-related diseases has stimulated the search for compounds able to promote mitochondrial functionality. Our study was designed to evaluate the effect of a white grape juice extract (WGJe) on mitochondrial activity, in an ex vivo experimental model consisting of activated lymphocytes obtained from a younger age group and an older age group of subjects. WGJe steadily decreased the lymphocytic mitochondrial mass in the older subjects, without a relevant effect in their younger counterpart, and significantly enhanced Δψm in both groups investigated. Finally, WGJe reduced the endogenous mitochondrial production of H2 O2 in all subjects. The results support the potential use of WGJe to improve mitochondrial functionality, thus maintaining human health and slowing down aging. Graphical Abstract: